Cardiac solitary fibrous tumor – an extremely rare but potentially fatal diagnosis - Szot, Mateusz; Zub, Aleksandra; Kurzawa, Paweł; Janus, Magdalena; Goszczyńska, Ewa; Jemielity, Marek; Perek, Bartłomiej (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2024)
The background of this review is a description of the case of a 28-year-old man with an extremely rare cardiac solitary fibrous tumor (SFT). Although this tumor was removed surgically and in the 6-month follow-up examination no relapse was noted, recurrence was observed and confirmed in the magnetic resonance imaging 4 months later. SFT prevalence, symptoms and signs, treatment options and prognosis are reviewed.